Targeting Autophagy for the Treatment of Alzheimer’s Disease: Challenges and Opportunities - Liu, Jie; Li, Lian (Frontiers in Molecular Neuroscience, 2019)
Alzheimer’s disease is the most common type of dementia which characterized by progressive loss of memory and cognitive function due to degeneration of synapses and axons. Currently, there is no cure for Alzheimer’s disease. Deposition of extracellular amyloid-β plaques and intracellular neurofibrillary tangles are two major hallmark pathologic changes in the brain of Alzheimer's patient. Autophagy is the major mechanism in cells responsible for removing protein aggregates. Anormalous immature autophagic vacuoles accumulated in dystrophic neurites in Alzheimer patient's brain suggests that autophagy process is disturbed. It is not yet clear whether autophagy plays a causative role, a protective role or just a consequence of the disease process itself. Understanding the exact role of autophagy in different stages of Alzheimer’s disease progression may help to design more effective therapeutic strategies towards this devastating disorder.